Enhancing MSME Marketing Capability through Digital-Based Mentoring in the Processed Food Sector - Dodi Ria Atmaja; Fachmi Tamzil (Yayasan Darussalam Bengkulu, 2025)
This community service program aims to enhance the marketing capability of micro, small, and medium enterprises (MSMEs) through digital-based mentoring in the processed food sector. The main problem faced by MSMEs is the limited ability to utilize digital platforms for marketing activities, resulting in restricted market reach and low competitiveness. The program employed a participatory approach consisting of training, practical implementation, and intensive mentoring focused on digital marketing strategies, branding, and content development. The activity involved 30 MSME actors and was conducted in West Jakarta. The results show a significant improvement in participants’ understanding and skills in using digital platforms, managing marketing content, and strengthening product branding. In addition, there was a shift in marketing practices from conventional methods to more structured and digital-based approaches, leading to broader market reach and greater business opportunities.Therefore, digital-based mentoring is proven to be an effective and practical approach to improve MSME marketing capabilities and support business transformation toward more competitive and sustainable market development.